ORGANIZATIONAL RESILIENCE AS A MEDIATOR BETWEEN INDIVIDUAL AND GROUP RESILIENCE AND ORGANIZATIONAL PERFORMANCE: EVIDENCE FROM THE BALI REGIONAL OFFICE OF THE DIRECTORATE GENERAL OF TAXES - I Nengah Brate; Komang Krisna Heryanda; M. Rudi Irwansyah (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study examines the role of organizational resilience in mediating the influence of individual resilience and group resilience on organizational performance at the Bali Regional Office of the Directorate General of Taxes. The population comprised 351 employees serving as Account Representatives, Functional Tax Examiners, and State Tax Bailiffs, from which 89 respondents were selected using probability sampling with a simple random sampling technique. This research employed a quantitative design grounded in the positivist paradigm. Data were collected through structured questionnaires and analyzed using Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) approach. The results indicate that individual resilience and group resilience do not have a significant direct effect on organizational performance; however, both variables significantly strengthen organizational resilience, which in turn has a significant positive effect on organizational performance. Furthermore, organizational resilience fully mediates the relationship between individual and group resilience and organizational performance, indicating that improving organizational performance in public sector institutions depends on strengthening organizational resilience systems that integrate individual and team adaptive capacities.